Time series of hospital admissions for burns in pediatric patients in the Southern Region of Brazil in the period from 2016 to 2020 - Thiago Gonçalves Souza; Kellen Meneghel de Souza (Revista Brasileira de Cirurgia Plástica, 2022)
Introduction: Burns are considered global public health problems and have a higher incidence in underdeveloped countries. In Brazil, it is estimated that 1,000,000 accidents involving burns occur annually. In pediatric patients, burns are the second most common cause among incidents that occur in childhood, being the third cause of death in them. This study aimed to analyze the rates of hospital admissions for burns in pediatric patients in the southern states, from 2016 to 2020. Methods: Ecological time series study, with data obtained in the southern region of Brazil, using the database of data from the Hospital Information System of the Unified Health System, from 2016 to 2020. To analyze temporal trends, standardized morbidity coefficients and the simple linear regression method were used. Results: From 2016 to 2020, there were 8,256 hospitalizations of children and adolescents victimized by burns in the southern region of Brazil, with the state of Paraná being responsible for the highest rates throughout the study period. The main age group involves preschool children aged 1-4 years (n=4748); regarding gender, most of the child sample is predominantly male (n=5.205). Conclusion: There is a trend towards stability in the overall hospitalization rate. Males and the age group of 1-4 years are the most affected by burns in southern Brazil. Paraná has higher hospitalization rates when compared to other states.